A novel ensemble machine learning and time series approach for oil palm yield prediction using Landsat time series imagery based on NDVI. Issue 25 (13th December 2022) - Ang, Yuhao; Shafri, Helmi Zulhaidi Mohd; Lee, Yang Ping; Abidin, Haryati; Bakar, Shahrul Azman; Hashim, Shaiful Jahari; Che'Ya, Nik Norasma; Hassan, Mohd Roshdi; Lim, Hwee San; Abdullah, Rosni
Abstract: Accurate oil palm yield prediction is necessary to sustain oil palm production for food security and economic return. However, there are limited studies on comprehensive mapping and accurate oil palm yield prediction using advanced machine learning algorithms. Using multi-temporal remote sensing data, this paper proposed a new approach to predict oil palm yield based on the normalized difference vegetation index (NDVI) and ensemble machine learning algorithm. ReliefF algorithm with linear projection was employed to select the best combination of spectral indices in oil palm discrimination. Oil palm land cover was classified using random forest (RF) and modified AdaBoost algorithms. A time-series approach known as walk-forward validation was firstly introduced to train the model using the 2016-2019 data and the one-step prediction was performed for 2020 using RF and AdaBoost. Result of the study revealed that the RF model (RMSE = 0.384; MSE = 0.148; MAE = 0.147) outperformed the AdaBoost model (RMSE = 0.410; MSE = 0.168; MAE = 0.176). Our research has demonstrated the value of detailed mapping and subsequent yield prediction by developing a novel approach utilising time-series satellite imagery, ensemble machine learning, and NDVI, which will assist decision-makers in managing their practices related to oil palm.